2022
DOI: 10.7150/ijms.70435
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of functional biomolecules-enriched foods on human health: A randomized controlled clinical trial

Abstract: Naturally occurring milk compounds have recently been investigated for their health-promoting properties; in fact, their anti-microbial, immuno-modulatory, antioxidant and anti-thrombotic activities, have increasingly gained interest within the scientific community. We have reported a translational, randomized, controlled clinical trial (RCT) on human subjects with a moderate to high cardiovascular risk, and a body mass index (BMI) >25.1 kg/m2, to evaluate the clinical impact of biomolecules-enriched Mediterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In the contest of emerging epigenetic modulators, several studies have demonstrated the effects of the natural antioxidant δ-valerobetaine (δVB), N , N , N -trimethyl-5-aminovaleric acid [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], a water-soluble trimethylated compound originating from a specific transformation of Nε-trimethyllysine [ 24 , 25 ]. Experimental studies suggest that δVB has great potential in the prevention of diabetes and its vascular complications, with many effects occurring through the modulation of the epigenetic regulators, SIRT1 and SIRT6 [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the contest of emerging epigenetic modulators, several studies have demonstrated the effects of the natural antioxidant δ-valerobetaine (δVB), N , N , N -trimethyl-5-aminovaleric acid [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], a water-soluble trimethylated compound originating from a specific transformation of Nε-trimethyllysine [ 24 , 25 ]. Experimental studies suggest that δVB has great potential in the prevention of diabetes and its vascular complications, with many effects occurring through the modulation of the epigenetic regulators, SIRT1 and SIRT6 [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in research in buffalo milk due to its bioactive substance content and health benefits. As the therapeutic potential of the bioactive compounds in buffalo milk is proven, interest in buffalo milk is increasing all over the world (Colarow et al, 2003;Servillo et al, 2018;D'Onofrio et al, 2019;Tatullo et al, 2022). Compared with fermented cow's milk products, those made with buffalo milk have been found to show better bacterial viability in vitro gastrointestinal digestion, and buffalo milk has been reported to have a potential protective effect on the human microbiome (da Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional drugs, functional foods have a higher safety profile and higher adherence. The functional foods market has rapidly increased, attracting attention from consumers and merchants (12). Thus, designing novel functional foods has become a topic of focus.…”
Section: Introductionmentioning
confidence: 99%